2017
DOI: 10.1186/s12885-016-3027-1
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic vaccine targeting Epstein-Barr virus latent protein, LMP1, suppresses LMP1-expressing tumor growth and metastasis in vivo

Abstract: BackgroundIn endemic area, nasopharyngeal carcinoma (NPC) tumor cells harbor EBV latent infection and expresses viral antigens such as EBNA1, LMP1 and LMP2. In this study, we established a NPC-mimicry animal model and assessed the therapeutic potential of LMP1 vaccine.MethodsAnimal models were established by injection of LMP1-expressing TC-1 cells in C57BL6/J mice subcutaneously or through tail veins. pcDNA3.1 empty vector or LMP1/pcDNA3.1 vaccine was delivered by a helium-driven gene gun. Effectiveness of vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 31 publications
(39 reference statements)
1
13
0
2
Order By: Relevance
“…287 The construction of in vivo models could be divided into spontaneous models, induced models, transplantation models, and transgenic models. [288][289][290][291][292] Spontaneous models are rarely obtained and utilized. 288 Induction conforms to the characteristics of tumor dynamics and is often used to screen carcinogens but seldom used in targeted therapy for NPC.…”
Section: Discussionmentioning
confidence: 99%
“…287 The construction of in vivo models could be divided into spontaneous models, induced models, transplantation models, and transgenic models. [288][289][290][291][292] Spontaneous models are rarely obtained and utilized. 288 Induction conforms to the characteristics of tumor dynamics and is often used to screen carcinogens but seldom used in targeted therapy for NPC.…”
Section: Discussionmentioning
confidence: 99%
“…For examples, Fu and colleagues demonstrated that EBNA1 peptide-loaded DCs vaccine elicited CD4+ T-cells responses and tumour growth inhibition using several EBNA1-expressing BL mouse models including wild-type B6, CD8-deficient, and MHC class I-deficient mice [ 66 ]. Recently, Lin and coworkers successfully suppressed LMP1-enhanced NPC tumour growth and metastasis by injecting LMP1 vaccine into C57BL6/J mice [ 16 ]. Furthermore, the LMP1 vaccine was able to prevent LMP1-expressing tumour development when it was given before tumour challenge [ 16 ].…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%
“…Recently, Lin and coworkers successfully suppressed LMP1-enhanced NPC tumour growth and metastasis by injecting LMP1 vaccine into C57BL6/J mice [ 16 ]. Furthermore, the LMP1 vaccine was able to prevent LMP1-expressing tumour development when it was given before tumour challenge [ 16 ]. Notably, the outcome of animal model is important to test out the feasibility of new immunotherapy or vaccine, but it must not be related to any of clinical trial outcomes due to the biological variations across different models.…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA vaccines have previously reported interesting responses against LMP1 [28] and LMP2 [29] in mouse models. This study furthers this research by exploring the immune responses to a combination of EBV latent proteins using newly designed synthetic DNA-encoded antigens studied in the context of facilitated in vivo local delivery.…”
Section: Introductionmentioning
confidence: 99%